Arguments from Ignorance, Coverage, and Bubbles - Bondy, Patrick (Informal Logic, 2026)
In “Epistemic Coverage and Argument Closure,” Catherine Hundleby brings together Sanford Goldberg’s work in social epistemology with Douglas Walton’s work in argumentation theory, on the topic of arguments from ignorance and truth-to-testimony conditionals. This paper explores the uses and limits of such arguments and conditionals, especially in connection with the problem of epistemic bubbles.